2014
DOI: 10.1158/0008-5472.can-13-3311-t
|View full text |Cite
|
Sign up to set email alerts
|

miR-30-5p Functions as a Tumor Suppressor and Novel Therapeutic Tool by Targeting the Oncogenic Wnt/β-Catenin/BCL9 Pathway

Abstract: Wnt/β-catenin signaling underlies the pathogenesis of a broad range of human cancers, including the deadly plasma cell cancer multiple myeloma (MM). In this study, we report that downregulation of the tumor suppressor microRNA miR-30-5p is a frequent pathogenetic event in MM. Evidence was developed that miR-30-5p downregulation occurs as a result of interaction between MM cells and bone marrow stromal cells, which in turn enhances expression of BCL9, a transcriptional co-activator of the Wnt signaling pathway … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
164
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(173 citation statements)
references
References 45 publications
6
164
2
Order By: Relevance
“…In the last few years, a wealth of studies has shown deep dysregulation of miRNAs in human cancers, including multiple myeloma (3). Importantly, replacement of downregulated tumor suppressor (TS) miRNAs (4,5) or inhibition of oncogenic miRNAs (6)(7)(8) have demonstrated therapeutic value in multiple myeloma preclinical settings. A subclass of TSmiRNAs, named epi-miRNAs, is emerging as novel epigenetic regulators, which target and downregulate the expression of DNA methyltransferases (DNMT), histone deacetylases (HDAC), or components of the polycomb repressor complexes, thus representing relevant tools to revert epigenetic aberrations.…”
Section: Introductionmentioning
confidence: 99%
“…In the last few years, a wealth of studies has shown deep dysregulation of miRNAs in human cancers, including multiple myeloma (3). Importantly, replacement of downregulated tumor suppressor (TS) miRNAs (4,5) or inhibition of oncogenic miRNAs (6)(7)(8) have demonstrated therapeutic value in multiple myeloma preclinical settings. A subclass of TSmiRNAs, named epi-miRNAs, is emerging as novel epigenetic regulators, which target and downregulate the expression of DNA methyltransferases (DNMT), histone deacetylases (HDAC), or components of the polycomb repressor complexes, thus representing relevant tools to revert epigenetic aberrations.…”
Section: Introductionmentioning
confidence: 99%
“…BCL-9 is broadly associated with MM cell proliferation, survival, migration and drug resistance. More importantly, BCL-9 regulates Wnt target genes that control transition and stem cell-like behavior with a negligible effect on the homeostatic role of Wnt signaling in mammalian (24,27). These results suggest that the strategies employed on the restoration of PCDH10 can be a potential therapy to refractory and recurrent patients without a particular effect on normal tissues.…”
Section: Discussionmentioning
confidence: 93%
“…The absorbance (A) at 450 nm was measured using a spectrophotometer (Bio-Rad, Richmond, CA, uSA). For Wnt treatment, the cells were pretreated with Licl for 48 h to activate Wnt/β-catenin signaling (27). Experiments were performed at least three times with representative data presented.…”
Section: Semi-quantitative Reverse Transcription Pcr (Rt-pcr) and Quamentioning
confidence: 99%
See 1 more Smart Citation
“…The manipulation of miRNAs has been showed to undermine cancer progression. The reactivation of tumor suppressor miRNAs, such as miR-29b or miRNA-30-5p, in myeloma cells, has therapeutic effects (40,41). On the other hand, miR-21 has been demonstrated to have an oncogenic feature (42).…”
Section: Microrna As Therapeutic Targetmentioning
confidence: 99%